First-line treatment for patients with advanced non-small cell lung carcinoma and high PD-L1 expression: pembrolizumab or pembrolizumab plus chemotherapy. Issue 1 (3rd May 2019) - Zhou, Yixin; Lin, Zuan; Zhang, Xuanye; Chen, Chen; Zhao, Hongyun; Hong, Shaodong; Zhang, Li
Abstract : Pembrolizumab monotherapy has become the preferred treatment for patients with advanced non-small cell lung carcinoma (NSCLC) and a programmed cell death-ligand 1 (PD-L1) tumor proportion score (TPS) of at least 50%. However, little is known about the value of adding chemotherapy to pembrolizumab in this setting. Therefore, we performed an indirect comparison for pembrolizumab plus chemotherapy versus pembrolizumab, using the frequentist methods. The primary outcomes were overall survival (OS), progression-free survival (PFS) and objective response rate (ORR). Data were retrieved from randomized trials comparing pembrolizumab plus chemotherapy or pembrolizumab monotherapy against chemotherapy. Five trials involving 1289 patients were included. Direct meta-analysis showed that both pembrolizumab plus chemotherapy (ORR: relative risk (RR) 2.16; PFS: hazard ratio (HR) 0.36; OS: HR 0.51) and pembrolizumab alone (ORR: RR 1.33; PFS: HR, 0.65; OS: HR 0.67) improved clinical outcomes compared with chemotherapy. Indirect comparison showed that pembrolizumab plus chemotherapy was superior to pembrolizumab alone, in terms of ORR (RR 1.62, 1.18–2.23) and PFS (HR 0.55, 0.32–0.97). A trend towards improved OS was also observed (HR 0.76, 0.51–1.14). In conclusion, the addition of chemotherapy to pembrolizumab further improves the outcomes of patients with advanced NSCLC and a PD-L1 TPS of at least 50%.